The effect of direct and indirect corrective feedback on students’ spelling errors (2011)
The study presented here is an attempt to examine the role of indirect feedback in promoting junior high school students’ spelling accuracy in English. It compares the effect of direct feedback with indirect feedback on students’ written work dictated by their teacher from their textbooks. Two classes were selected from the Zanjanrood District in Iran. Forty-four male students in two groups, one from School A (the direct feedback group) and the other from School B (the indirect feedback group) were treated differently regarding their spelling errors for six weeks. The results obtained revealed that indirect feedback is a more effective tool than direct feedback in rectifying students’ spelling errors.El estudio que aquí se reporta busca examinar el papel de la retroalimentación indirecta, en la promoción de la precisión en la escritura en inglés, de estudiantes de educación secundaria. Se comparan los efectos de la retroalimentación directa e indirecta en los trabajos escritos de los estudiantes, provenientes de los libros de texto y de dictados hechos por el profesor. Se seleccionaron dos grupos del Distrito Zanjanrood en Irán a los que se les dio, durante seis semanas, un tratamiento distinto respecto a sus errores de ortografía. En total, eran cuarenta y cinco estudiantes de sexo masculino, distribuidos en dos grupos: uno de la Escuela A (el grupo que recibió retroalimentación directa) y otro de la de la Escuela B (el grupo que recibió retroalimentación indirecta). Los resultados mostraron que la retroalimentación indirecta es una herramienta más efectiva que la directa, cuando se trata de rectificar los errores de ortografía de los estudiantes.